American sniper [videorecording (DVD)] - Cooper, Bradley; Miller, Sienna, 1981-; Grimes, Luke, 1984-; Kyle, Chris, 1974-2013; DeFelice, Jim, 1956-; McEwen, Scott (Warner Bros. Entertainment, 2015)
U.S. Navy SEAL Chris Kyle is sent to Iraq with only one mission: to protect his brothers-in-arms. His pinpoint accuracy saves countless lives on the battlefield. However, his reputation is also growing behind enemy lines, putting a price on his head and making him a prime target of insurgents. He is also facing a different kind of battle on the home front: striving to be a good husband and father from halfway around the world.